DOWNLOADING SUPERIOR REGIONAL PRODUCTS FOR ECONOMIC EMPOWERMENT WOMAN BASED EQUALITY GENDER FOR PUSH NUMBER VIOLENCE INSIDE THE HOUSE STAIRS IN FAKFAK DISTRICT - Ruhaya La Abukena; Sundjoto Sundjoto; Untung Tamsil; Titis Istiqomah (Jurnal Scientia, 2023)
Domestic violence against women is a classic problem in the world, generally caused Because helplessness economy from race Woman That Alone. On the side On the other hand, women have great potential as business actors on an economic scale and own many fundamental capabilities in creating superior products to accelerate acceleration regional economic growth. The research aims to find pressing implementation strategies number violence in House ladder public regency Fakfak through empowerment women's economy by creating superior regional products. Research conducted for 8 months from May to December 2023. Combination research method with Partial Least Square analysis approach where the results are described using diagrams Ishikawa. Effort technical find form action use analysis SWOT-balanced scores cards. Respondent study chosen in a way on purpose. Technique taking data use questionnaire Which served in a way closed by researcher together team surveyor, with use indicator For devising techniques weighting.